Blockchain Infrastructure and Growth of Global Power Consumption - Denisova, Valeriia; Mikhaylov, Alexey; Lopatin, Evgeny (International Journal of Energy Economics and Policy, 2019)
The paper proposes the link between cryptocurrency implementation in the financial sector and energy consumption worldwide. The underlying mechanism of this blockchain infrastructure is described, practical cases of its adoption in various segments of the financial sector are provided. This paper tries to explain the power consumption of the cryptocurrency mining at the case of Bitcoin, Ethereum, Monero, Litecoin. Since mining is not regulated by the state, and even banned in some countries, it is difficult to find accurate data on how much electricity is spent on it. Method of Herfindahl–Hirschman is used for efficiency estimate of crypto market. Keywords: energy consumption, mining pools, bitcoin, blockchain, cryptocurrency, cloud mining. JEL Classifications: G32, G34, O33. DOI: https://doi.org/10.32479/ijeep.7685